Teachers' perception about inclusion at the Autonomous University of Nayarit. Opportunity or challenge? - Enciso Arámbula, Dra. Rosalva; Estrada Esquive, Dra. Ana Luisa; Arvizu López, Dra. Bertha Alicia (Transformación, 2021)
Objective: The paper aims at exploring positive and negative perception of Social Sciencesteachers at the UAN about the inclusion of Special Educational Needs (SEN) students in the classroom.Method: The researchers rely on a quantitative, descriptive, transversal and non-experimental approach, following a simple random probability sampling, with a margin of error of 5% and a confidence level of 95%. The population was 185 of Social Sciences teachers at the UAN, the sample was 126 participants. Result: Teachers consider inclusion positive regarding the right that young people have to join regular class; However, they consider their lack of abilities to assist SEN students as a negative item; they are not currently given any training, require extra time to teach them, and observe such students do less efforts than needed to learn.Conclusion: 84% of teachers have assisted at least one young person with special educational needs, without having sufficient training. They believe it would be better for SEN students to attend specialized centers instead of to going to a university.
Keywords: Inclusive education; learning disabilities; special education; education of students with special needs